Karola Bloch in East Germany (GDR, 1950-55). Standardisation of Childcare Facilities as a Women’s Emancipatory Tool - Siegele, Bettina (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2022)
The architect Karola Bloch, who was working for the Deutsche Bauakademie in the GDR after World War II, aimed to meet the goal of gender equality according to socialist principles by realising numerous crèches and kindergartens through the development of schematic plans and guidelines for building construction. For the newly founded socialist state of the GDR, this was a way to free women from domestic unpaid care work in order to integrate them into wage-earning labour, which was considered crucial for women to become equal members of society. The implementation of a nationwide network of childcare centres via typification and standardisation promised to realise these ambitious goals quickly and cost-effectively.